Effect of selected dietary supplements on growth performance andproduction of pond reared deccan mahseer, Tor khudree (Sykes, 1839) - Basade, Yasmeen; Kohli, M P S; Ogale, S N (Indian Journal of Fisheries, 2016)
The effect of selected dietary supplements on the growth performance, survival, production, body composition and digestiveenzyme activityÂ  in deccan mahseer reared under pond conditions was stuided. Cholicalciferol (CC), soylecithin (SL), thyroxine(TH) and betaine (BT) were added to the basal diet (BD) asÂ  supplements at concentrations of 1800 IU kg-1, 3.5%, 0.05ppmand 0.5% respectively. After a rearing period of 180 days on experimental diets, soylecithin supplemented diet (SL) resultedin significantly higher (p